Performance of the LHCb outer tracker in run-I and run-II of the LHC - Bachmann, Sebastian (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2024)
The LHCb experiment is designed to study B-decays at the LHC. It is constructed as a forward spectrometer. The large particle density in the forward region poses extreme challenges to the sub-detectors in terms of hit occupancy and radiation tolerance. To accurately and efficiently detect the charged decay particles in the high-density particle environment of the LHC the Outer Tracker (OT) has been constructed. The OT is a gaseous straw tube detector, consisting of 53,760 straw tubes, covering a total area of 360 m2 with double layer modules. The performance of the OT during run I and run II of the LHC from 2010 to 2018 will be presented. Experiences from the detector operation and the performance in terms of hit resolution and hit efficiency are presented.
Online veröffentlicht: 4. September 2024, Artikelversion: 12. September 2024
Gesehen am 27.02.2025